Implementation of Tax Planning to Minimize Income Tax Article 21 - Sabrina, Dewi; Pramukti, Andika; Rosmawati, Rosmawati (Advances in Taxation Research, 2024)
Purpose: This study examines implementing tax planning strategies to minimize Income Tax Article 21 obligations at Dana Pensiun Perkebunan (DAPENBUN) while ensuring regulatory compliance and financial efficiency. Research Design and Methodology: This research uses a qualitative approach and relies on primary data collected through interviews and documentation. Data analysis involves organizing, interpreting, and evaluating tax policies and implementation at DAPENBUN PTPN XIV. Findings and Discussion: The study finds that DAPENBUN PTPN XIV applies the gross-up method for employee income tax Article 21, where tax allowances are included in taxable income and covered by the company. Only pension contributions and BPJS Ketenagakerjaan (employment insurance) employees pay are excluded from taxation. Meanwhile, retiree income tax follows the gross method, where pensioners bear the tax burden. Certain cash benefits, such as uniforms, medical expenses, and recreation allowances, have been converted into in-kind benefits to reduce taxable income. Implications: This study highlights the role of strategic tax planning in reducing corporate tax burdens while maintaining compliance. It provides insights for pension funds and businesses seeking to enhance tax governance and financial management.